SIKAP BAHASA MASYARAKAT BANJAR DALAM RANAH KELUARGA DAN PEMERINTAH KABUPATEN KOTABARU KECAMATAN PULAU LAUT UTARA - Husni Mubarak (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2016)
This study aimed Knowing the tendency to use language Banjar in the realm of family and the Government in the District of North Sea island of Kotabaru district and the existence of language Banjar Knowing the dimensions of attitude official language as a communication tool in the realm of family and the Government in the District of North Sea island Kotabaru District. This method will dideskriptipkan about the linguistic phenomenon, in particular with regard to the attitude of Banjar community language in the realm of family and government. The use of qualitative methods are chosen with consideration of qualitative adjustment method is easier than the complex reality and presenting a direct relationship between researcher and respondent, as well as more sensitive and can adjust for natural language Banjar present data directly. Based on the analysis of the data that has been shown, can be submitted following conclusions: (1) The trend in the use of language Banjar district specific PLU in the realm of family showed the phenomenon of language attitude is predominantly uses language Banjar. Furthermore, in the realm of government to demonstrate that language is flexible or relay (language Banjar, and Indonesia). (2) .Eksistensi dimensional attitude toward language Banjar Banjar community language in the realm of family illustrates that language Banjar used consistently. It is characteristic of positive language. While in the realm of language Banjar Government indicated the existence of language use are less consistent with other signs of the negative language, this seems to use language that diverse and flexible. Keywords: attitude and language banjar